The Role of School Principals to Improve Teacher Professionalism in Indonesia: A Systematically Literature Review - Mubin, Holikul; Muhayani, Ulfah; Syahputri, Ghifari Sasmita Mutiara Ayu; Ahnaf, Sherly Amanda; Amrullah, Mohammad Haekal Izzat (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the role of school principals in improving teacher professionalism in Indonesia through a systematic review method. The data was gathered from various indexed sources, including Google Scholar, Publish or Perish indexed by PubMed, Crossref, and Semantic Scholar, using keywords such as "The Role of School Principal" and "Teacher Professionalism." A total of 64 relevant articles were identified, with 15 meeting the inclusion criteria. The findings reveal that principals enhance teacher professionalism by implementing various strategies, such as academic supervision, professional development programs, mentoring, and a supportive work environment. Principals act as leaders, motivators, supervisors, and facilitators, guiding teachers to enhance their competencies through training, workshops, and continuous professional development. The study concludes that strengthening the leadership capacity of school principals is essential to promoting teacher professionalism and improving educational outcomes in Indonesia.